An Inexpensive, 3D-Printable, Arduino- and Blu-Ray-Based Confocal Laser and Fluorescent Scanning Microscope - Justin Loose; Samuel H. Hales; Jonah Kendell; Isaac Cutler; Ryan Ruth; Jacob Redd; Samuel Lino; Troy Munro (Metrology)
There is a growing field that is devoted to developing inexpensive microscopes and measurement devices by leveraging low-cost commercial parts that can be controlled using smartphones or embedded devices, such as Arduino and Raspbery Pi. Examples include the use of Blu-ray optical heads like the PHR-803T to perform cytometry, spinning disc microscopy, and lensless holographic microscopy. The modular or disposable nature of these devices means that they can also be used in contaminating and degrading environments, including radioactive environments, where replacement of device elements can be expensive. This paper presents the development and operation of a confocal microscope that uses the PHR-803T optical device in a Blu-ray reader for both imaging and detection of temperature variations with between 1.5 and 15 µm resolution. The benefits of using a PHR-803T confocal system include its relatively inexpensive design and the accessibility of the components that are used in its construction. The design of this scanning confocal thermal microscope (SCoT) was optimized based on cost, modularity, portability, spatial resolution, and ease of manufacturability using common tools (e.g., drill press, 3D printer). This paper demonstrated the ability to resolve microscale features such as synthetic spider silk and measure thermal waves in stainless steel using a system requiring <USD 1000 in material costs.